(untitled) (The NOUN Journal of Agricultural Research and Development (NJARD), 2025)
This study evaluated the effects of graded levels of monosodium glutamate (MSG) administered orally on the growth performance of male rabbits. Thirty-two mongrel bucks (average weight 1039 ± 15.6 g) were housed in a completely randomized design at the University Teaching and Research Farm, Federal University Dutse, Jigawa State. Rabbits were fed commercial pelletized growers MAXX diet and water ad libitum. After 14 days of acclimatization, they were assigned to four treatments of eight rabbits each. A stock solution was prepared by dissolving 40 g MSG in 1 L of distilled water. Group 1 served as control and received 2 ml distilled water only, while Groups 2, 3, and 4 received 2, 4, and 6 ml MSG/kg BW, respectively, administered orally every 48 hours for 56 days using a round-head syringe. Initial body weights showed no significant differences (P > 0.05) among groups. However, rabbits in T3 (4 ml MSG) recorded significantly (P < 0.05) higher final weight (3037.60 g), total weight gain (2002.40 g), and average daily gain (35.75 g) compared with other treatments. Daily and total feed intake were significantly (P < 0.05) influenced by MSG, with the highest values (126.13 g/day; 7063.30 g total) observed in T4 (6 ml MSG). Feed conversion ratio (FCR) was significantly (P < 0.05) poorer in T4 (4.29). It was concluded that oral administration of MSG at 4 ml/kg BW enhanced rabbit performance, and its use at this level is recommended.